2021
DOI: 10.24815/eej.v12i3.19080
|View full text |Cite
|
Sign up to set email alerts
|

The strategies applied by teachers in teaching speaking

Abstract: The teaching of English is very important for young learners in the era of industry 4.0. A successful teacher is largely determined by the strategies he/she uses in the learning process. The students in SMP Negeri 1 Sabang were very interested in speaking English. They had won many events in English speaking competitions and mostly reached a good score on speaking test. This research was conducted to find out the strategies used, problems, and the solutions faced by the teachers during a teaching process at SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…The percentage of learners' interest in the two schools is not significantly different, which is 36% of students in Waru and 38% in Malaysia. This finding supports previous research conducted by Aslan 18 ; Lisa 19 ; Chen & Chan 20 ; Yüksel et al 21 ; Maulidar & Samad 22 . This identifies that vocabulary learning strategy by utilizing flashcards is suitable for young learners.…”
Section: Sanggar Bimbingan Malaysiasupporting
confidence: 92%
“…The percentage of learners' interest in the two schools is not significantly different, which is 36% of students in Waru and 38% in Malaysia. This finding supports previous research conducted by Aslan 18 ; Lisa 19 ; Chen & Chan 20 ; Yüksel et al 21 ; Maulidar & Samad 22 . This identifies that vocabulary learning strategy by utilizing flashcards is suitable for young learners.…”
Section: Sanggar Bimbingan Malaysiasupporting
confidence: 92%
“…The research findings showed that the strategies can stimulate students to speak up and be more actively engaged in the learning processes. Third, indeed similar to previous study, a study which committed by Maryanti, Gani & Marhaban (2021) also disclosed that the English teacher used various types of teaching strategies such as role-play, picture description, interview, and simulation. In addition, this study also revealed some obstacles in teaching and learning processes such as the inability of teacher to completely control students, the passivity of students in learning process, low respect for classmates, limited study duration and lack of vocabulary mastery.…”
supporting
confidence: 80%
“…Recognizing these differences is crucial in designing effective teaching strategies that cater to the diverse needs of both personality types (Rahayu, 2020). The success of language teaching lies in employing suitable strategies that align with the goals of communication skill development (Maulidar et al, 2019). Ryan and Mercer (2012) underscore the pivotal role of teachers' strategies in determining the success or failure of language learning.…”
Section: Literature Reviewmentioning
confidence: 99%